Reframing Da'wah Communication: Communicative Accommodation and Legitimacy Construction among the Baduy Muslim Community - Saragih, Fadhila Azmi; Bakti, Andi Faisal (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This study examines how da’wah communication is negotiated within the indigenous socio-cultural context of the Baduy Muslim community in Desa Kompol, Kanekes Village, Lebak Regency, Indonesia. Rather than conceptualizing da’wah as a process of unilateral religious transmission, the study approaches it as a culturally embedded communicative practice through which relational legitimacy, religious meaning, and communicative authority are continuously negotiated within indigenous symbolic systems. Employing an interpretive qualitative design, data were generated through semi-structured interviews, participant observation, and document analysis involving eleven religious actors, including Muhammadiyah-affiliated da’i, NU-associated da’i, local religious leaders, and foundation-based volunteers engaged in da’wah activities among the Baduy Muslim community. The findings reveal three interconnected patterns. First, communication accommodation enables religious actors to negotiate relational access and legitimacy through sustained interpersonal engagement while remaining subject to indigenous customary authority. Second, indigenous symbols, rituals, and cultural meanings are selectively renegotiated within Islamic ethical frameworks through gradual symbolic accommodation rather than direct doctrinal confrontation. Third, religious legitimacy emerges through the interaction of relational engagement, institutional preparation, and ongoing negotiation with indigenous authority structures, making legitimacy conditional rather than permanently secured. The study contributes to intercultural communication and da’wah scholarship by demonstrating that religious communication in indigenous settings operates as a dynamic process of communicative accommodation, symbolic negotiation, and legitimacy construction rather than a linear transmission of religious doctrine.